PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KOMITMEN PEGAWAI PADA RUMAH SAKIT UMUM PROVINSI NUSA TENGGARA BARAT - Rosya Wardani; Baiq Ertin Helmida (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
Organizational commitment is a form of identification, loyalty and involvement expressed byemployees to the organization. Employees who have good commitment mean that the employee hasloyalty to the organization where he is currently and will strive to try to achieve the goals of theorganization where he works optimally. The pattern of work with monotonous basic tasks leads toboredom, lack of initiative and the low driving force of an employee certainly has an impact on theservice quality.Partial testing results (t test) show that the independent variables (work motivation, workdiscipline, job satisfaction) partially or simultaneously have a significant effect on the employeescommitment of the NTB Provincial Hospital. while Adjusted R Square (R2) of 0.696 shows that workmotivation, work discipline, and job satisfaction are able to explain variations in influence on employeescommitment of 69.6%.